Elevated methemoglobin levels in patients treated with hydroxocobalamin: a case series and in-vitro analysis. (2nd September 2022) - Kiernan, Emily Anne; Carpenter, Joseph E.; Dunkley, Camille A.; Moran, Tim P.; Rothstein, Lindsay Schaack; Silver, Elizabeth; Salehi, Maryam; Koch, David D.; Morgan, Brent W.; Murray, Brian Patrick
Abstract: Background: Historically, the first step in treating cyanide (CN - ) toxicity utilized antidotes to induce methemoglobinemia. This is concerning in patients who are already hypoxemic or have elevated carboxyhemoglobin. Hydroxocobalamin (OHCbl) is now the first-line antidote for CN - toxicity and is not known to induce methemoglobinemia. We observed elevated methemoglobin (MetHb) levels in several patients treated with OHCbl and sought to investigate the incidence of MetHb formation following administration of OHCbl. Methods: Chart review: A single-center, retrospective case series of patients who received 5 or 10 g of hydroxocobalamin from 01/01/2011 through 04/30/2019. Data was analyzed using descriptive statistics. In-vitro study: Discarded blood was separated into whole blood and plasma samples. OHCbl and normal saline was added to reach 0×, 1×, 2×, and 4× peak therapeutic concentrations and analyzed at times 0, 2, and 4 h after administration. Results: Chart review: Twenty-seven cases of OHCbl administration were identified. The median age was 53 years (IQR 38 − 64) and 20 (74.1%) were male. Exposure to a house fire or smoke inhalation was the reason for OHCbl administration in 21 (77.8%) patients. Five (18.5%) patients received 10 g of OHCbl while the rest received 5 g. Six (22.2%) patients developed methemoglobinemia, all after 5 g OHCbl administration; four had been exposed to fire and smoke, two received the medication for severe acidosis of unknown etiology not related to fire or smoke. The median peak level was 7.1% (IQR 2.2 − 16.4%) at a median time of 11.4 h post-administration. Two patients received methylene blue (MB), neither responded. Death occurred in 17 (63%) cases. In-vitro study: We observed a dose dependent elevation in total hemoglobin but did not detect any increase in MetHb. Conclusion: We observed a noteworthy temporal association between the formation of methemoglobinemia and the administration of hydroxocobalamin. This does not appear to be an artifact of the CO-oximeters. This could have profound implications for patients who are already hypoxemic or have impaired oxygen carrying capacity from carboxyhemoglobin.